The Influence of Double Loop Problem Solving (DLPS) Technique to Teach Reading Comprehension Achievement of The Tenth Grade Students of SMA Negeri 1 Belitang Jaya - Risa, Risakristia; Kuspiyah, Hastuti Retno; Muklas, Muhamad (English Education Program, Education Faculty, Universitas Nurul Huda, 2022)
This thesis is entitled “The Influence of Double Loop Problem Solving (DLPS) Technique to Teach Reading Comprehension Achievement of The Tenth Grade Students of SMA Negeri 1 Belitang Jaya